Temporal reliability and stability of delay discounting: A 2-year repeated assessments study of the Monetary Choice Questionnaire - Strickland, Justin C; Gelino, Brett W; Rabinowitz, Jill A; Ford, Magdalene R; Dayton, Lauren; Latkin, Carl; Reed, Derek D (Experimental and clinical psychopharmacology, 2023)
The Monetary Choice Questionnaire (MCQ) is one of the most commonly used measures to assess delay discounting of reward. Reliable measurement by the MCQ is necessary for use in experimental settings or prognostic validity within clinical contexts. The present analysis expands prior work to evaluate temporal reliability and stability over an extended period, including repeated measurements, a larger and more broadly representative sample, and demonstrations of covariation with clinically significant health behaviors (e.g., cigarette use, COVID-19 vaccination, body mass index). Participants ( = 680; 55.6% female) were recruited through crowdsourcing and completed the MCQ approximately quarterly over 2 years. Measures of reliability, stability, and correlations with clinical constructs were determined for each timepoint and pairwise comparison. Test-retest reliabilities were high across all pairwise comparisons (all > .75; range = .78-.86; mean = .83). Stability was also high with within-subject effect size differences all within a less-than-small effect size range (range = -0.09 to 0.19; mean = 0.04). Positive associations between smoking status and delay discounting rates were observed consistent with prior clinical studies. These findings of test durability support the use of MCQ administration for repeated measurement of delay-constrained choice as a stable respondent characteristic and illustrate its association with important health behaviors over extended time periods. (PsycInfo Database Record (c) 2023 APA, all rights reserved).